Fimbria-specific antibodies detach Escherichia coli from human cells. - Mett, H (1983)
Antibodies obtained from rabbits immunized with purified adhesion-mediating fimbriae of Escherichia coli SS142 were specific for the fimbriae of the homologous strain; they did not cross-react with isolated fimbriae of three different E. coli strains or with protein extracts from nine other adhesive E. coli strains. The antibodies inhibited adhesion to Intestine 407 tissue culture cell monolayers and hemagglutinating activity of E. coli SS142 but not of several other E. coli strains. The antibodies were able not only to prevent but also to reverse the adhesion of E. coli SS142 to Intestine 407 cells or human erythrocytes. Analysis of the kinetics of inhibition suggested that the antibodies did not competitively inhibit adhesion. Such antibodies can be useful for distinguishing different mechanistic steps of bacterial adhesion. Their ability to reverse bacterial adhesion in vitro may be of clinical relevance.